Cost-Effectiveness of an Economic Empowerment and Family Intervention on Mental Health Among School-Going Adolescent Girls in Uganda, 2017‒2022. - Ssewamala, Fred M.; Tozan, Yesim; Brathwaite, Rachel; Kiyingi, Joshua; Namatovu, Phionah; Bahar, Ozge Sensoy; Nabunya, Proscovia; Nartey, Portia B.; Neilands, Torsten B. (American Journal of Public Health, 2025)
Objectives. To assess the cost-effectiveness of an economic empowerment and family intervention on mental health outcomes among school-going adolescent girls in Uganda from 2017 to 2022. Methods. We randomized adolescent girls aged 14 to 17 years into 3 arms: (1) health and sex education (usual care; n = 408), (2) youth development accounts (YDAs; n = 471), and (3) a combination intervention (YDA plus multiple family group [MFG]; n = 381). We fitted mixed-effects models and estimated intervention costs prospectively using the microcosting approach. Results. The combination intervention had a statistically significant impact on mental health outcomes (depressive symptoms, hopelessness, self-concept) at 12 and 24 months, except self-esteem at 24 months, relative to usual care, with incremental cost‒effectiveness ratios ranging from $51 to $100 per 0.2-SD change at 12 months, and $53 to $157 at 24 months per 0.2-SD change. Conclusions. The combination intervention positively and significantly impacted a higher number of mental health outcomes among school-going adolescent girls compared with YDA alone. The benefits were sustained in the short and long term, with the incremental cost-per-unit effect remaining comparable. Findings support the integration of combination interventions in school settings to promote adolescent girls' positive mental health functioning.